PENGARUH WORD OF MOUTH DAN CELEBRITY ENDORSER DALAM MENGOKOHKAN BRAND AWARENESS DAN BRAND ATTITUDE - Nurdin, Herry (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research aims to analyze the influence of words of mouth and celebrity endorsers to brand awareness and brand attitude. It also examines the influence of words of mouth and celebrity endorserson brand attitude through the consumersâ brandawareness in Top Coffee, Mataram. The population of this research was the Top Coffeeâs in Mataram City. There wehe 100 respondents, the sample was taken using purposive sampling technique. The data were analyzed with Structural Equation Modeling (SEM). The results show that there was a positive and significantÂ correlation betweenÂ words of mouth and celebrity endorsersÂ towardÂ brand awareness and brand attitude.Â There was also insignificant or partially significant effect on the correlation of word of mouth andÂ celebrity endorsers toward brand attitude that was mediated by brand awareness. This research has both theoretical and managerial implications in the context of Top Coffee products.Â Key words: words of mouth, celebrity endorser, brand awareness, brand attitude